1991
DOI: 10.1111/j.1476-5381.1991.tb12440.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine inhibits ATP‐sensitive K+channels in mouse pancreatic β‐cells

Abstract: 1 The effects of clonidine and adrenaline on adenosine 5'-triphosphate (ATP)-sensitive K + channels were studied in pancreatic #-cells from normal mice.2 When perifused with a medium containing 1 mm glucose, many of the ATP-sensitive K+ channels in the fl-cell membrane are open. Under these conditions, clonidine (5-100,uM) reversibly decreased 86Rb efflux from the islets, whereas adrenaline was ineffective at concentrations up to 100,UM.3 In 6 mm glucose, most of the ATP-sensitive K + channels in the fl-cell m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…The whole cell mode of the patch clamp technique was 'ns then used to determine whether the drug directly affects the K+ATP channels (Figure 4). At the beginning of the trace, ATP-sensitive K+ currents are large because the cell interior has equilibrated with the pipette solution containing a low * concentration of ATP (Plant et al, 1991 Voltage-dependent K+ channels were studied in the whole cell mode, by depolarizing the P cell membrane from -70 to 0 mV. As shown in Figure 5, 100 AM genistein also reversibly inhibited these channels.…”
Section: Measurements Of Cyclic Amp Inositol Phosphates and Adenine mentioning
confidence: 99%
See 2 more Smart Citations
“…The whole cell mode of the patch clamp technique was 'ns then used to determine whether the drug directly affects the K+ATP channels (Figure 4). At the beginning of the trace, ATP-sensitive K+ currents are large because the cell interior has equilibrated with the pipette solution containing a low * concentration of ATP (Plant et al, 1991 Voltage-dependent K+ channels were studied in the whole cell mode, by depolarizing the P cell membrane from -70 to 0 mV. As shown in Figure 5, 100 AM genistein also reversibly inhibited these channels.…”
Section: Measurements Of Cyclic Amp Inositol Phosphates and Adenine mentioning
confidence: 99%
“…Ca2e currents were recorded by the perforated patch technique. Experimental details and composition of the solutions used have been described previously (Plant et al, 1991). In some experiments, the extracellular solution contained mg ml' BSA.…”
Section: Electrical Recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, the mechanism of action of imidazoline insulinsecretagogues has not been fully established, and their principal molecular target has not been defined at the level of the ␤-cell. Convincing evidence is available that imidazolines can regulate the efflux of K + ions from the ␤-cell (14)(15)(16)(17)(18), and several studies have indicated that the pore-forming subunit of the K ATP channel, Kir6.2, may be an imidazoline binding protein (18)(19)(20). This conclusion first emerged from electrophysiological studies performed in heterologous expression systems (18,19) but has also been confirmed more directly, using an affinity chromatographic approach in which endogenous Kir6.2 was selectively retained on an efaroxanconjugated affinity matrix (20).…”
mentioning
confidence: 99%
“…It has now been established, however, that the primary determinant of this secretagogue activity is not a2-antagonism per se, but rather the possession of an imidazoline ring within the molecule. Thus, certain other imidazolines which are not a2-antagonists also have insulin secretagogue activity (Schulz & Hasselblatt 1989a); as does clonidine, which is an M2-adrenoceptor agonist (Schulz & Hasselblatt, 1989b;Plant et al, 1991).…”
Section: Introductionmentioning
confidence: 99%